2020
DOI: 10.1016/j.devcel.2020.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Potently Cytotoxic Natural Killer Cells Initially Emerge from Erythro-Myeloid Progenitors during Mammalian Development

Abstract: Highlights d NK cell potential arises from erythro-myeloid progenitors (EMPs) in the yolk sac d EMP-derived NK cells, similar to fetal NK cells, have a potent degranulation response d hPSC differentiation yields 2 distinct CD34 + populations, each with NK cell potential d hPSC-derived EMP-like NK cells are more potently cytotoxic than adult CD16 + NK cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 53 publications
2
58
0
Order By: Relevance
“…Following the initial wave of primitive blood progenitors arising in yolk sac blood islands, a second wave of HSC-independent hematopoietic progenitors is detected around E8. This wave produces erythro-myeloid progenitors (EMPs) that are largely restricted to erythroid, megakaryocyte, and myeloid lineages, though some studies have suggested rare B-lymphocyte potential as well as NK-cell potential (McGrath et al, 2015;Dege et al, 2020). EMPs are distinguished from the primitive wave by their generation of adult-like enucleated erythrocytes with a distinct globin gene expression profile, as well as by their ability to generate granulocytes in addition to macrophages (McGrath and Palis, 2008).…”
Section: Erythromyeloid Progenitors Arise From Hemogenic Endothelium mentioning
confidence: 99%
“…Following the initial wave of primitive blood progenitors arising in yolk sac blood islands, a second wave of HSC-independent hematopoietic progenitors is detected around E8. This wave produces erythro-myeloid progenitors (EMPs) that are largely restricted to erythroid, megakaryocyte, and myeloid lineages, though some studies have suggested rare B-lymphocyte potential as well as NK-cell potential (McGrath et al, 2015;Dege et al, 2020). EMPs are distinguished from the primitive wave by their generation of adult-like enucleated erythrocytes with a distinct globin gene expression profile, as well as by their ability to generate granulocytes in addition to macrophages (McGrath and Palis, 2008).…”
Section: Erythromyeloid Progenitors Arise From Hemogenic Endothelium mentioning
confidence: 99%
“…Sources of primary NK cells used in these clinical trials to treat both hematologic malignancies and solid tumors include peripheral blood (PB)-derived, umbilical cord blood (UCB)-derived, and induced pluripotent stem cell (iPSC)-derived NK cells (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). However, despite clinical use of these diverse NK cell populations, there is relatively little known about key phenotypic, genotypic, and functional comparison between these NK cell populations that may lead to difference in clinical efficacy (10,(13)(14)(15)(16). NK cells were first described as a lymphocyte population able to detect and rapidly kill tumor cells or viral infected cells without prior sensitization (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Groups have successfully differentiated pluripotent stem cells (PSCs) into NK cells that are similar in phenotype and effector function when compared to primary NK cells [80,81,89,[92][93][94][95][96][97][98]. The differentiated cells express several NK-associated receptors such as CD56, KIRs, CD16, NKp44, NKp46, NKG2D, and TRAIL [80,82,[92][93][94][95].…”
Section: Manufacturing Nk Cells From Ipscsmentioning
confidence: 99%
“…However, it is unclear if the derived cells resemble the bright or dim subset of the CD56 population, suggesting that further investigation into the expression profile of differentiated NK cells may be necessary. A recent study by Dege et al further probed the ontogeny of hPSC-derived NK cells and found two distinct CD34 + populations that dictate final effector function [97]. The HOXA neg/low /CD34 + progenitors gave rise to a population that exhibits more potent degranulation while the HOXA + /CD34 + progenitors resulted in an NK population with robust inflammatory cytokine secretion [97].…”
Section: Manufacturing Nk Cells From Ipscsmentioning
confidence: 99%
See 1 more Smart Citation